Job satisfaction and retention of midwives in rural Nigeria. Issue 10 (October 2015) - Adegoke, A.A.; Atiyaye, F.B.; Abubakar, A.S.; Auta, A.; Aboda, A.
Abstract Background Nigeria is one of the 57 countries with a critical shortage of human resources for health, especially in remote rural areas and in northern states. The National Midwifery Service Scheme (MSS) is one approach introduced by the Government of Nigeria to address the health workforce shortage in rural areas. Since 2009, unemployed, retired and newly graduated midwives are deployed to primary health care (PHC) facilities in rural areas of Nigeria. These midwives form the mainstay of the health system at the primary health care level especially as it relates to the provision of skilled attendance at birth. This study followed up and explored the job satisfaction and retention of the MSS midwives in three Northern states of Nigeria. Methods this was a descriptive study. Data were collected using a mixed method approach which included a job satisfaction survey, focus group discussions (FGDs) and exit interviews to explore job satisfaction and retention factors. All 119 MSS midwives deployed by the National Primary Health Care Development Agency between 2010 and 2012 to the 51 Partnership for Reviving Routine Immunisation- Maternal and Child Health (PRRINN-MNCH) programme targeted PHC facilities were included in the study. Results MSS midwives were very satisfied with from the feeling of caring for women and children in the community (4.56), with the chance to help and care for others (Mean 4.50), the feeling of worthwhile accomplishment from doing the job (Mean 4.44) and the degree of respect and fair treatment they received from more senior staff and/or supervisor (Mean 4.39). MSS midwives were least satisfied with the lack of existence of a (established) career ladder (Mean 2.5), availability of promotional opportunities within the scheme (Mean 2.66), safety of accommodation (Mean 3.18), and with 'the degree to which they were fairly paid for what they contribute to the health facility' (Mean 3.41). When asked about future career plans, 38% (n=33) of the MSS midwives planned to leave the scheme within two years, of which 16 (18%) wanted to leave within one year. However, 39% of the midwives (n=34) indicated that they would be happy to continue working even after the scheme has ended. Of these 34 participants, 18 would like to continue working in the same facility where they are now whereas the remaining 16 would like to continue working in the north but not in the facility where they are working currently. Eight themes on job satisfaction and retention emerged from the FGDs conducted with current midwives, whereas six themes emerged from the exit interviews from midwives who have left the scheme. Conclusion the MSS programme is a short-term solution to increase SBA coverage in rural Nigeria. MSS midwives were dissatisfied with the short term contract, lack of career structure, irregular payment, poor working condition, inadequate supervision and poor accommodation being offered by the programme, which all contribute to poor retention of MSS midwives. Implications for policy and practice midwives׳ job satisfaction and retention are critical to improving the health of mothers and their newborn. Poor job satisfaction and retention therefore requires improvements in financial and non-financial incentives, health systems, supportive supervision, ensuring job security and a career structure for midwives working in rural health facilities. Initiating effective strategies to motivate and increase the retention of rural health workers is important for Nigeria to achieve the Millennium/Sustainable Development Goals.